Examining the behavior of crop‐derived antibiotic resistance genes in anaerobic sludge batch reactors under thermophilic conditions. Issue 11 (30th August 2019) - Gardner, Courtney M.; Volkoff, Savannah J.; Gunsch, Claudia K.
Abstract: The consumption of transgenic crops and their by‐products has become increasingly common in the United States. Yet, uncertainty remains regarding the fate and behavior of DNA within food matrices once it exits the digestive track and enters into wastewater treatment plants (WWTPs). Because many transgenic crops have historically contained antibiotic resistance genes as selection markers, understanding the behavior and uptake of these transgenes by environmental microbes is of critical importance. To investigate the behavior of free transgenic crop DNA, thermophilic anaerobic batch reactors were amended with varying concentrations of transgenic crop genes (i.e., LUG, nptII, and bla ) and the persistence of those genes was monitored over 60 days using quantitative PCR. Significant levels of nptII and bla were detected in extracellular DNA (eDNA). Furthermore, LUG maize marker genes were also detected in the control reactors, suggesting that other crop‐derived transgenes contained within digested transgenic foods may also enter WWTPs. Possible bacterial transformation events were detected within the highest dose treatments at Days 30 and 60 of incubation. These findings suggest that within the average conventional digester residence times in the United States (30 days), there is a potential for bacterial transformation events to occur with crop‐derived transgenes found in eDNA. Abstract : The consumption of transgenic crops and their by‐products has become increasingly common in the United States. Yet, uncertainty remains regarding the fate and behavior of DNA within food matrices once it exits the digestive track and enters into wastewater treatment plants.